The strange case of the victim who did not want justice - Mégret, Frédéric (International journal of transitional justice, 2018)
Transitional justice and particularly criminal justice efforts within it are heavily reliant on victim support and a certain ability to speak ‘in the name of’ victims. This article explores the complex figure of the ‘reluctant victim’ by reexamining the legal treatment of Argentine children illegally ‘adopted’ during the dictatorship and who refused to submit themselves to DNA testing. Such cases, it is argued, should be seen as emblematic of the ambivalence of many victims in transitional contexts, particularly when it comes to prosecutions. Moreover, they have a significant conceptual antecedent in debates among feminists on how to treat intimate partner violence and the rise of ‘mandatory punishment policies,’ which can help shed light on the broader relationship of transitional justice and criminal justice to notions of victimhood, and the challenges of rendering justice for victims against their expressed will.